Review and development of the contribution ratio of indoor climate (CRI) - Weirong Zhang; Yanan Zhao; Peng Xue; Kunio Mizutani (Energy and Built Environment, 2022)
An indoor thermal environment is affected by various heat elements, such as heat transfer through walls, solar radiation, and heat emissions from people, lighting and equipment. To promote both local thermal comfort and building energy efficiency, demand-oriented ventilation (such as personalized ventilation) has been developed. When using this method, a good understanding on indoor temperature distribution becomes necessary. For this purpose, an index known as Contribution Ratio of Indoor Climate (CRI) has been developed through extraction from the calculation results of Computational Fluid Dynamics (CFD). This index can be used to analyze the independent contribution of each heat element to indoor temperature distribution. In this paper, a complete and detailed introduction of the CRI is given, including its basic premises, definitions, and mathematical meaning. Particularly, calculation method of the CRI in natural convection airflow fields is further developed. Two cases (forced and natural convection airflow fields) have been carried out in different scenarios, with results showing that the CRI of a heat source had higher values in the area around itself. Also, it had a larger influence range in forced convection airflow field because of the convective airflow, while relatively larger CRI values only appear in the area above the heat source in the natural convection airflow field because of the heat plume. As a useful index for understanding the form of indoor temperature field, the CRI has guiding significance for regulating air-conditioning/ventilation systems to build better indoor thermal environment.